GREAT DISRUPTION IN SOUTHERN SOCIETY AS REFLECTED IN JOHN GRISHAM'S THE TESTAMENT - Tatit Hariyanti (Celt: A Journal of Culture, English Language Teaching & Literature, 2008)
At the dawn of the twentieth century. especially after the invention of internet the world began to transform itself into information age which was characterized by the production more of two things people value most in a modern democracy -freedom and equality. Freedom of choice has exploded and hierarchies of all sorts, have come under pressure and begun to crumble. People were trapped in a globalized and homogenous condition. Accompanying the shift there arouses social disorders which is indicated especially by the decline of family values. As that of other industrialized countries, when the United States becomes more advanced it is assumed that all its states experience the same condition. There seems no place for distinctive feature. The southern states which always claim and are claimed to be distinctive from the rest will . therefore. be interesting and worth observing. Taking John Grisham's work. The Testament. which is set in Virginia in the year of J 996s, as the main source, this study is done under the notion that literary works could serve as mental evidence of what happens in society. The result demonstrates that Southern society experience the same condition. The increasing individualism in turn exerts great influence on the family life. The bond becomes more loosen and distrust rises.